Simplified Modeling of Isolated Bridges With Triple Friction Pendulum Bearings Using Opensees - NOUR, RAWAN ALI (İstanbul Kültür Üniversitesi, 2022)
Many recent studies and research have been concerned with the issue of seismic isolation and its importance for our buildings, but very few of them have concentrated on this issue regarding bridges even though bridges are important as residential buildings or even more. Therefore, further studies of seismic isolation for highway bridges will lead to a better understanding of this concept. Especially the seismic response of these isolated bridges should be studied to learn the importance of this issue and discover its gaps and weaknesses to improve this concept and apply it on a larger scale. In this paper, we are going to study the seismic response of an existing bridge that is isolated seismically by using a special type of sliding components isolator which is: "The Triple Friction Pendulum Bearings". The seismic behavior of the bridge will be examined in two conditions: fixed and isolated base structure simultaneously through time history analysis using the OpenSees software. Furthermore, Nodal displacement of the selected bridge, the base shear and the force-displacement hysteresis loops of the isolation system are presented graphically under three earthquake ground motion records. The findings of the study are summarized in the conclusion section.
Üçlü Sürtünmeli Sarkaç Mesnetli Sismik Yalıtımlı Köprüler Deprem Yükleri Altında Davranışı
▪ Yüksek lisans tezi.
Keywords: Seismic Isolation; Triple friction pendulum bearings; OpenSEES; Seismic Response; Ground Motion